BLOOD LEAD LEVELS AS RISK FACTOR FOR PREECLAMPSIA IN ASIAN CONTINENT: A SYSTEMATIC REVIEW - Risha Meilinda Marpaung; Ema Hermawati (Jurnal Kesehatan Tambusai, 2023)
Preeclampsia is a hypertensive disorder in pregnancy which complicates around 2-8% of all pregnancies in the world. Based on estimates from the World Health Organization (WHO), the prevalence of preeclampsia in developing countries is seven times higher than in developed countries. Preeclampsia also causes death of pregnant women in Africa and Asia, around 9%. Increased serum lead levels of pregnant women are associated with an increased risk of preeclampsia. This systematic review study aims to review articles discussing whether blood lead levels are a risk factor for preeclampsia in Asian Continent. This research is a systematic review using PRISMA guidelines. Articles were obtained from several scientific databases, such as Pubmed, Google Scholar, ProQuest, Scopus, and Science Direct (published between 2015 and 2022), using relevant keywords including ("Blood Lead" OR "Lead exposure") AND ("Risk factor") AND ("Preeclampsia") AND ("Pregnant women" OR "Pregnant mother"). Majority of article exposures have the same results regarding the effects of lead exposure in pregnant women with preeclampsia in various countries on the Asian Continent. Results showed that there was significant increase in blood lead levels in the group of pregnant women with preeclampsia compared to pregnant women without complications. We conclude that lead in the blood can be a risk factor for preeclampsia in pregnant women on the Asian Continent. Further research is highly expected to assess the relationship between lead exposure and preeclampsia in pregnant women through experimental studies with larger study samples in the exposed and unexposed groups.